1986
DOI: 10.1159/000249221
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinemia Type II in Two Cases Previously Reported as Richner-Hanhart Syndrome

Abstract: Two sibs with palmo-plantar keratosis and dendritic corneal opacities, previously described as suffering from Richner-Hanhart syndrome by other authors, about 25 years ago, showed increased plasma and urine tyrosine levels. Their neurological and mental features were within normal limits. A comprehensive review of the literature showed a total of 47 cases of fully documented tyrosinemia type II; 8 more patients also had the clinical features of the disease, but aminoacidemia had never been observed. The import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…A literature review of all cases reported in the PubMed Database during the last 30 years, and the new patients reported in this study, resulted in Table . Families and patients were numbered according to the previous report, which comprised 56 cases in 42 families, adding 87 new subjects belonging to 63 families, resulting in a total of 142 cases representing 105 families, and a carrier individual representing 1 additional family (XCII). The table also includes some patients that have been genotyped subsequent to their previous description, so they have been numbered according to their first listing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review of all cases reported in the PubMed Database during the last 30 years, and the new patients reported in this study, resulted in Table . Families and patients were numbered according to the previous report, which comprised 56 cases in 42 families, adding 87 new subjects belonging to 63 families, resulting in a total of 142 cases representing 105 families, and a carrier individual representing 1 additional family (XCII). The table also includes some patients that have been genotyped subsequent to their previous description, so they have been numbered according to their first listing.…”
Section: Resultsmentioning
confidence: 99%
“…Skin symptoms are mostly represented by painful hyperkeratotic plaques of soles and palms, which usually develop after the first year of life, although they may appear earlier. Intellectual disability is a relatively common feature but may be mild or absent …”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis can easily be established by high plasma levels of tyrosine, with other plasma amino acid levels being normal. 10,17 Tyrosine is the only amino acid increased in the urine of these patients. TAT activity is reduced or absent in supernatant of liver homogenates.…”
Section: -16mentioning
confidence: 92%
“…2,6,17 There is no relationship between age of diagnosis and mental retardation. However, the degree of mental retardation may be related to higher values of plasma tyrosine.…”
Section: -16mentioning
confidence: 99%
“…The skin lesions may occur as early as 6 weeks of age or as late as 6 years [1,7,9,10]. They appear as discrete hyperkeratotic papules and plaques with an irregular border.…”
Section: Introductionmentioning
confidence: 99%